2021
DOI: 10.1037/ppm0000321
|View full text |Cite
|
Sign up to set email alerts
|

What babies, infants, and toddlers hear on Fox/Disney BabyTV: An exploratory study.

Abstract: Sound and music are integral components of screen content. Yet, little research has been undertaken exploring soundscapes of infant-directed broadcasts. The current study implements a soundscape analysis of a representative corpus broadcast on Fox/Disney BabyTV for young children between the ages of 0 and 3 years; we considered both musical and linguistic constituents as structural components of the soundscape. The current study randomly selected 1 episode from each of the 39 series broadcast on the BabyTV cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…van den Heuvel et al (2019) state that screen exposure may not be appropriate for children younger than 30 months, since they are not capable of learning language from it; secondly, it has been found that, in general, TV shows directed to young children are not actually appropriate for their age range. Brodsky and Sulkin (2020) analysed the music and sound of episodes of series for 0‐ to 3‐ year‐olds and discovered that, although they seem to attract children, they do not promote screen interactions and, as a result, do not contribute to their cognitive development. Moreover, as linguistic constituents are for the most part unintelligible utterances, no opportunity is created for the kid to develop a more comprehensible language.…”
Section: Discussionmentioning
confidence: 99%
“…van den Heuvel et al (2019) state that screen exposure may not be appropriate for children younger than 30 months, since they are not capable of learning language from it; secondly, it has been found that, in general, TV shows directed to young children are not actually appropriate for their age range. Brodsky and Sulkin (2020) analysed the music and sound of episodes of series for 0‐ to 3‐ year‐olds and discovered that, although they seem to attract children, they do not promote screen interactions and, as a result, do not contribute to their cognitive development. Moreover, as linguistic constituents are for the most part unintelligible utterances, no opportunity is created for the kid to develop a more comprehensible language.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was not the case that some unrealistic elements were more common in books as opposed to videos; videos were more unrealistic across the board. This might be due to the fact that the video medium inherently has more methods for presenting unrealistic content, as videos can contain unrealistic sounds and movements in addition to linguistic and visual depictions (Brodsky & Sulkin, 2020). This content analysis used identical coding categories for books and videos to facilitate direct comparisons between these two types of media, but future work should aim to characterize more precisely how unrealistic soundscapes or other aspects of a story’s depiction may contribute to its overall level of unrealism.…”
Section: Discussionmentioning
confidence: 99%